Spiritual activities, institutional adjustment, stress and coping mechanism of inmates at the Bureau of Jail Management and Penology, Iloilo City. - Pahila, Rheinhart G, Sta. Maria, Joce; Sta. Maria, Joce R.
The study was conducted to describe the involvement of the inmates in different spiritual activities to determine the stressors and to describe the different coping strategies they employ inside the institution. Thirty two (32) inmates served as respondents for the study. They were incarcerated for more than a day and not more than ten years. Three instruments were utilized namely: Spiritual Questionnaire adapted from Social Weather Station Survey (1991), Carver COPE (1989) and the Qualitative Interview on Stress and Coping adapted from doctoral dissertation of Partyka (2004). Results of the study revealed that inmates are involved in different spiritual activities which include solitary worship, group devotions, church attendance , church-based activities and observation of religious sacraments. Majority of the inmates utilized the emotion-focused form of coping strategy. Most of them reported that the main cause of their stress is physical heat experienced inside their respective cell.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Inmates -- Bureau of Jail Management and Penology -- Iloilo City; Inmates -- Coping mechanisms